Optimizing market reach through digital marketing: A Study on the National Amil Zakat Agency (BAZNAS) Malang City - mubarak, israul (Maliki Interdisciplinary Journal, 2025)
Zakat is one of the pillars of Islam that plays an important role in the lives of Muslims, both spiritually and socio-economically. Although Indonesia has great zakat potential, zakat collection is still very low, one of the causes of which is the lack of awareness of zakat and low public trust in zakat institutions. In the digital era, information technology is the key to increasing zakat collection through digital marketing. This study aims to analyze how BAZNAS Malang City can utilize digital marketing to optimize zakat collection and expand market reach. The method used in this study is a qualitative approach through interviews and literature studies from previous studies that are relevant to the study. The results of the study show that BAZNAS Malang City has succeeded in implementing an effective digital marketing strategy, by utilizing social media such as Instagram and TikTok as well as integrating direct and indirect fundraising. This strategy has been proven to expand the reach of the zakat market, increase ZIS fundraising, and strengthen the image of the institution in the eyes of the public.